Implementation Of C4.5 Algorithm To Analyze Library Satisfaction Visitors: Implementation Of C4.5 Algorithm To Analyze Library Satisfaction Visitors - Fristi Riandari; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2020)
Measuring visitor satisfaction, especially in the library, is very important to note considering the library is a means intended to help the academic process or add insight to visitors. Measuring library visitor satisfaction is very important to note whether the services expected by visitors are in accordance with what is received, which will greatly assist the university in processing the library so that it can be used properly, so that the books provided can be of maximum use and not only the quality of service provided for the library provided can be an attraction for visitors to become fond of visiting the library reading books that will help academically the average visitor is a student. The system needed is the Data Mining Application in Measuring Satisfaction of library visitors at STMIK Pelita Nusantara. Where library visitors will be objects that provide an assessment / opinion on variables that have characteristics, namely Tangiable, Reability, Responsivnes, Assurance, Empathy. This system was built with the C4.5 algorithm and the Testing system with the application RapidMiner Studio 9.7.